Accumulation and re-distribution of microplastics via aquatic plants and macroalgae - A review of field studies. (May 2023) - Huang, Sirui; Jiang, Ruitong; Craig, Nicholas J.; Deng, Hua; He, Wenhui; Li, Juan-Ying; Su, Lei
Abstract: The aquatic plants and macroalgae are primary producers with major roles regarding the maintenance of ecosystems but their interaction with microplastics (MPs) has received less attention than animals. We summarize the methodologies used, the MPs abundances and their characteristics across the literature on MPs pollution in aquatic plants and macroalgae. The sampling and quantification of MPs still lacks consistency between studies, which increased the uncertainty in cross-comparisons. The abundance of MPs varied by orders of magnitude between species and were mostly fibers and polymers with large degrees of production and applications. Filamentous species contained more MPs than others. The average ratio of MPs between vegetated and unvegetated sites reached 3:1. The average ratio of MPs between the biotic and abiotic fractions reached 2193:1, suggesting a high level of retention in fields. Our findings supported that aquatic plants and macroalgae are critical in the plastic flux within the marine environments. Graphical abstract: Image 1 Highlights: The aquatic plants and macroalgae are critical in healthy eco-systems. Microplastics can get into the interior tissues of aquatic plants and macroalgae. Compared to unvegetated sites, vegetated sites had 1–5.7 times higher microplastics. Filamentous species contained more microplastics due to the entanglement. Ratios of microplastics between the biotic and abiotic fractions reached 2193:1.